Preferensi Perubahan Awal Waktu Subuh pada Komunitas Masjid - Firdaus FIrdaus; Fitra Nelli; Desminar Desminar; Bakhtiar Bakhtiar; Hasanuddin Hasanuddin (University of Muhammadiyah Sumatera Utara, 2022)
The Qur'an and Sunnah do not provide digital time specifications other than providing natural signs such as sunset as the beginning of the Maghrib prayer time and sunrise as the beginning of the Fajr prayer time. In modern times, the determination of prayer has used a digital system, so that prayer times are determined based on the rotation of time in a 24-hour circle. For example, the Fajr time for the Padang City area as of January 2021 and the previous year, the majority is at 05.00 WIB. Meanwhile, the results of the latest research found that at 05.00 it was not yet dawn so that Muslims prayed Fajr outside the specified time. This study uses the Falakiah approach, which aims to explore the response of the community and mosque community in the city of Padang to the change in the dawn time which has been going on since March 2021. The research data will be analyzed through reduction, display, and verification techniques. The results of the study show that there are those who accept that there is a fatwa from MUI and the government and there are still doubts because they follow the Muhammadiyah calendar of West Sumatra.